2018
DOI: 10.1126/scisignal.aar2125
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β–mediated enhancement of T H 17 cell generation is inhibited by bone morphogenetic protein receptor 1α signaling

Abstract: The cytokines of the transforming growth factor-β (TGF-β) family promote the growth and differentiation of multiple tissues, but the role of only the founding member, TGF-β, in regulating the immune responses has been extensively studied. TGF-β is critical to prevent the spontaneous activation of self-reactive T cells and sustain immune homeostasis. In contrast, in the presence of proinflammatory cytokines, TGF-β promotes the differentiation of effector T helper 17 (T17) cells. Abrogating TGF-β receptor signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…Interestingly, this indicates a potential interaction between SMAD4 and ETS or RUNX transcription factors that are important regulators of T cell differentiation and homeostasis ( 29 , 30 ), exemplifying that SMAD4 interacts with different partners to mediate its wide transcriptional impact in CD8 + T cells. Notably, BMP and activin, other members of the TGF-β family that signal through SMAD4, have been proposed to alter the biology of CD4 + T cells ( 31 , 32 ). However, treatment of either naive CD8 + T cells or activated CD8 + T cells with either BMP or activin failed to enforce the TGF-β–independent function of SMAD4 and alter the ability of TGF-β to induce CD103 expression ( Supplemental Figure 14 , A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this indicates a potential interaction between SMAD4 and ETS or RUNX transcription factors that are important regulators of T cell differentiation and homeostasis ( 29 , 30 ), exemplifying that SMAD4 interacts with different partners to mediate its wide transcriptional impact in CD8 + T cells. Notably, BMP and activin, other members of the TGF-β family that signal through SMAD4, have been proposed to alter the biology of CD4 + T cells ( 31 , 32 ). However, treatment of either naive CD8 + T cells or activated CD8 + T cells with either BMP or activin failed to enforce the TGF-β–independent function of SMAD4 and alter the ability of TGF-β to induce CD103 expression ( Supplemental Figure 14 , A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Tnfsf4 and Cd274 for instance can suppress IL-17A production in T cells 97,98 . Interestingly, adult cDC2 further showed higher expression of bone morphogenic protein 2 (Bmp2), which also suppresses IL-17A production from T cells 99 (Supplementary Fig. 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that activated Bone Morphogenic Protein Receptor 1α (BMPR1α)-deficient CD4+ T cells produce a large amount of IFN-γ and enhance tumor proliferation, indicating the adverse effect of BMP signaling on the adaptive immune response (53). Abrogation of BMPR1α signaling during CD4+ T cell activation induced inflammatory effector cells to express various of cytokines such as IL-17, IFN-γ, and TNF family and transcription factors defining the Th17 cell lineage (54). BMPs and BMPRs also serve an important role during the process of B cell activation (55).…”
Section: Os Sarc ----------------------------------------------------mentioning
confidence: 99%